Negative pressure pulmonary edema - a life-threatening condition in an eye care setting: a case report. (December 2016) - Venkatesh, Ramesh; Gautam, Preety; Dutta, Parul; Bala, Preeti
Abstract Background Negative pressure pulmonary edema is a potentially life-threatening complication after general anesthesia in young healthy individuals that results from upper airway obstruction followed by strong inspiratory effort. It is a known complication after nasal or upper airway surgery. Occurrence of such a life-threatening complication in an eye care setting where advanced intensive care is usually lacking is rare. Case presentation A 15-year-old Asian boy presented to our hospital with a penetrating eye injury caused by a pellet. Globe and vitreoretinal exploratory surgery was performed with the patient under general anesthesia. The patient's postoperative course was uneventful immediately after the procedure, but soon he developed negative pressure pulmonary edema. Conclusions This case report highlights the importance of early diagnosis and prompt management of negative pressure pulmonary edema to save the life of the patient. Most ophthalmologic surgeries are performed with the patient under regional anesthesia; very few are done with the patient under general anesthesia. Intensive care facilities are needed in such settings for prompt management of such a serious and rare complication.